Serum ferritin to detect iron deficiency in children below five years of age - Windy Saufia Apriyanti; Sutaryo Sutaryo; Sri Mulatsih (Indonesian Pediatric Society, 2013)
Background Iron deficiency (ID) anemia impacts thecognitive and motor development of children until the age of10 years, despite receiving iron therapy. Early det ection of IDis recommended and serum ferritin has been proposed as analternative indicator for ID det ection.Objective To assess th e diagnostic accuracy of serum ferritin fordetecting ID in children below five years of age.Methods T his cross-sectional, diagnostic study was conducted inprimary health care centers in Yogyakarta and Bantu!. Hemoglobin(Hb), serum ferritin and soluble transferrin receptor (sTfR) levelswere performed on children aged 6- 59 months.A sTfR level of 2:8.2 mg/L was used to define iron deficiency. T he best cutoff pointfor serum ferritin level use as a diagnostic tool was determined byreceiver operator curve.Results T he prevalence ofID was32%. Mean h emoglobin levelsin iron deficient and healthy children were 11.7 (SD 0.5) g/dL and12.2 (SD 0.7) g/dL, respectively. T he sensitivity, specificity, andpositive predictive value (PPV) of serum ferritin ( < 12 ug/L) were17%, 93%, and 56%, respectively. Using a cut off of <32.4 ug/L,serum ferritin had sensitivity of 62. l % and specificity of 50.8%.Conclusions The diagnostic value of serum fe rritin levels ismodestly capable of detecting ID. Therefore, serum ferritin shouldnot be used as an alternative indicator for detecting ID in childrenbelow five years of age.